Reviews - David Durling; Philip Barker; Gabriel Jacobs; James Milton; Robert Ward (Association for Learning Technology, 1996)
Although the range of research undertaken by universities and colleges covers a very wide spectrum, each of the books in this Kogan Page series is narrowly focused on a particular form of research, that of small-scale 'insider research'. This is defined as research into teaching and learning which is undertaken by tutors with the specific aim of improving their teaching practice. The series is intended to be quick and easy to read, to provide starting points for research into teaching practice, and to give pointers to ways in which outcomes may be recorded and published. It aims to deal with contemporary issues affecting teachers in colleges and universities, and to include a range of research methods with suggestions for how these might be used or adapted in particular circumstances. Each book in the series shares a version of the opening and concluding paragraphs. The opening paragraph introduces a concept of insider research based on the notion of the reflective practitioner of education: this model takes the view that teachers should play an active role in constructing and reconstructing knowledge with the aim of improving teaching. 'Research' is related mainly to the rating system defined by the Higher Education Funding Council for England (HEFCE).